Overexpression of VEGFα as a biomarker of endothelial dysfunction in aortic tissue of α-GAL-Tg/KO mice and its upregulation in the serum of patients with Fabry’s disease - Lund, N.; Wieboldt, H.; Fischer, L.; Muschol, N.; Braun, F.; Huber, T.; Sorriento, D.; Iaccarino, G.; Müllerleile, K.; Tahir, E.; Adam, G.; Kirchhof, P.; et al. (Frontiers in Cardiovascular Medicine, 2024)
Introduction Fabry's disease is an X-linked lysosomal storage disorder caused by reduced activity of α-galactosidase A (GAL), leading to premature death on account of renal, cardiac, and vascular organ failure. Accumulation of the GAL substrate globotriaosylceramide (Gb3) in endothelial and smooth muscle cells is associated with early vascular cell damage, suggesting endothelial dysfunction as a driver of cardiorenal organ failure. Here, we studied the vascular expression of the key angiogenic factors, VEGFα and its antagonist angiostatin, in Fabry α-GAL-Tg/KO mice and determined circulating VEGFα and angiostatin serum levels in patients with Fabry’s disease and healthy controls. Methods Cryopreserved aortic vessels from six α-GAL-Tg/KO and six wild-type (WT) mice were obtained and VEGFα and angiostatin levels were determined by performing Western blot analysis. VEGFα expression was visualized by an immunohistochemical staining of paraffin aortic rings. In addition, VEGFα and angiostatin serum levels were measured by using an enzyme-linked immunosorbent assay in 48 patients with genetically verified Fabry's disease (50% male) and 22 healthy controls and correlated with disease severity markers such as lyso-Gb3, albuminuria, NTproBNP, high-sensitive troponin T (hsTNT), and myocardial wall thickness. Results It was found that there was a significant increase in VEGFα protein expression (1.66 ± 0.35 vs. 0.62 ± 0.16, p = 0.0009) and a decrease in angiostatin expression (0.024 ± 0.007 vs. 0.053 ± 0.02, p = 0.038) in aortic lysates from α-GAL-Tg/KO compared with that from WT mice. Immunohistochemical staining revealed an adventitial VEGFα signal in α-GAL-Tg/KO mice, whereas no VEGFα signal could be detected in WT mice aortas. No differences in aortic angiostatin expression between α-GAL-Tg/KO- and WT mice could be visualized. The serum levels of VEGFα were significantly upregulated in patients with Fabry’s disease compared with that in healthy controls (708.5 ± 426.3 vs. 458.5 ± 181.5 pg/ml, p = 0.048) and positively associated with albuminuria (r = 0.82, p < 0.0001) and elevated NTproBNP (r = 0.87, p < 0.0001) and hsTNT values (r = 0.41, p = 0.048) in male patients with Fabry’s disease. For angiostatin, no significant difference was found between patients with Fabry’s disease and healthy controls (747.6 ± 390.3 vs. 858.8 ± 599.3 pg/ml). Discussion In conclusion, an overexpression of VEGFα and downregulation of its counter player angiostatin in aortic tissue of α-GAL-Tg/KO mice support the hypothesis of an underlying vasculopathy in Fabry's disease. Elevated VEGFα serum levels were also observed in patients with Fabry’s disease and were positively associated with elevated markers of organ manifestation in males. These findings suggest that angiogenetic markers, such as VEGFα, may be potentially useful biomarkers for the detection of endothelial dysfunction in classical Fabry's disease.